On Optimal Doubling in Backgammon - Zadeh, Norman; Kobliska, Gary (Management Science, 1977)
The concept of an effective doubling number for noncontinuous games is introduced. Computer simulation is employed to determine an extremely accurate strategy for accepting, doubling, and redoubling in running games.